Carbon intensity of the Japanese Iron and steel Industry: Analysis of factors from 2000 to 2019. (15th April 2022) - Oda, Junichiro; Akimoto, Keigo
Abstract: In this study, the factors influencing the carbon intensity (tCO2 /t crude steel) transition in the Japanese iron and steel industry from FY2000 to FY2019 were empirically evaluated. The results revealed that the upper processes (i.e., the hot-metal ratio, waste plastic, and waste tires), steel product mix, capacity factor, and linear time trend variable explain the actual carbon intensity trajectory reported for the years from FY2000 to FY2019. The upper process and capacity factor were found to be major contributors to the inter-annual fluctuations of carbon intensity. The coefficient of the capacity factor index (FY2005 = 100) was estimated to be −0.23% per 1 percentage point of the capacity factor, indicating that a 1% decrease in the capacity factor resulted in a 0.23% deterioration in the carbon intensity. The coefficient of the time trend variable was estimated to be −0.0034 tCO2 /t crude steel/y, which is equivalent to a 0.2%/y average improvement in carbon intensity over the period from FY2000 to FY2019. Because the observed improvement rate of carbon intensity was relatively small, a large-scale diffusion of innovative steelmaking processes such as hydrogen direct reduction will be required to achieve the goal of net zero emissions by 2050. Graphical abstract: Image 1 Highlights: Carbon intensity in the Japanese iron and steel sector (FY2000-FY2019) was analyzed. Factors influencing carbon intensity (tCO2 /t crude steel) transition were assessed. Hot metal ratio and capacity factor are major factors for inter-annual changes. The impact of the steel product mix on carbon intensity was explicitly evaluated. Carbon intensity improved by an average of 0.2%/y over FY2000-FY2019